A case study on methods used in the design of airport pavements / Hanizan Ma'arof - Ma'arof, Hanizan (1993)
The rapid development of aircraft types in recent years has had a profound effect on pavement design concept. Design engineers have uppermost in their mind the effect of vehicular traffic upon pavement structure. The design of airfields (airports) involves a study of the effect of the pavement upon the aircraft as well as the effect of the aircraft on the pavement. Types of aircraft load is one of the factors which affect the design of airfield pavement. Airport pavement are exposed to a much wider potential range in gross aircraft weights as compared to the effect of vehicular weights on highway pavement. As many airfield designs may be based upon a 20-30 life expectancy, the designer may be faced with the problem of selecting critical aircrafts that may not be in the planning phase of the aircraft industry.